Técnica de criação e parâmetros biológicos de Stegasta bosquella em amendoim - Boica Junior, Arlindo Leal [UNESP]; Ribeiro, Zulene Antonio [UNESP]; de Campos, Aniele Pianoscki [UNESP]; Chagas Filho, Norton Rodrigues [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2011)
Studies with Stegasta bosquella in peanut crop are little explored by researchers, mainly by the need of obtaining, in the field, a large quantity of closed leaflets. Therefore, it was sought a way of rearing in a natural diet that facilitates the attainment of the insect. The research was developed at the Laboratorio de Resistencia de Plantas a Insetos (FCAV/Jaboticabal) (T: 25 +/- 2 degrees C, RH 60 +/- 10% and photophase: 12 hours) (Runner IAC 886). The rearing stock of was carried out by collecting caterpillars from the field and keeping them in flat bottom glass tubes until adult emergence and test performance. Caterpillars were individualized in Petri dish plates, lined with moistened filter paper, which contained closed and early opened leaflets, but closed with paper clips (imitating the closed leaflet). A randomized design with two treatments and 36 repetitions was used. After the pupae formation, they were separated into five couples and the adults were kept in transparent plastic cages containing a peanut stem with leaves for oviposition, and fed with a 10% honey solution. The duration and viability of the larval and pupal periods, male and female longevity with and without food, and fertility were evaluated. The two forms of larvae rearing (closed leaflet and leaflet closed with clips) did not influence on any of the studied parameters. Therefore, the rearing of S. bosquella becomes feasible in natural diet, which means there is no need to use the enclosed leaflets for this purpose, and implies the easiness for rearing.

Estudos com Stegasta bosquella na cultura do amendoinzeiro são pouco explorados pelos pesquisadores, principalmente pela necessidade da obtenção, no campo, de grande quantidade de folíolos fechados. Diante disso, buscou-se uma forma de criação em dieta natural que facilite a obtenção do inseto. O ensaio foi desenvolvido no Laboratório de Resistência de Plantas a Insetos (FCAV/UNESP, Jaboticabal) (T: 25 ± 2 °C, UR: 60 ± 10% e fotofase: 12 horas). A criação estoque foi realizada coletando lagartas no campo e mantendo-as em tubos de vidro de fundo chato até a emergência dos adultos para, na geração seguinte, realizar o teste. Lagartas foram individualizadas em placas de Petri forradas com papel filtro umedecido, contendo folíolos fechados e folíolos recém abertos, porém fechados com clipes de papel (imitando o folíolo fechado), sendo estes folíolos da cultivar Runner IAC 886. Utilizou-se o delineamento inteiramente casualizado, com dois tratamentos e 36 repetições. Ao atingirem a fase de pupa, estas foram separadas em cinco casais e os adultos mantidos em gaiolas de plástico transparentes contendo uma haste de amendoim com folíolos para oviposição, alimentados com solução de mel a 10%. Avaliou-se a duração e a viabilidade dos estágios larval e pupal, a longevidade de machos e fêmeas com e sem alimento e a fecundidade. As duas formas de criação não influenciaram os parâmetros estudados. Com isso a criação de S. bosquella torna-se viável em dieta natural, não havendo a necessidade da utilização de somente folíolos fechados para isso, o que implica na facilidade de criação.
Rearing technique and evaluation of biological parameters of Stegasta bosquella in peanut
Keywords: Red-necked peanutworm; Rearing methodology; Arachis hypogaea